Photoelectrochemical Synthesis of Ammonia on the Aerophilic-Hydrophilic Heterostructure with 37.8% Efficiency - Zheng, Jianyun; Lyu, Yanhong; Qiao, M.; Wang, R.; Zhou, Y.; Li, H.; Chen, C.; Li, Y.; Zhou, H.; Jiang, San Ping; Wang, S. (CELL PRESS, 2019)
Liquid ammonia can be the key enabler for being an easily transported energy storage carrier, which is highly desirable to be produced from renewable energy, such as solar or electricity, under eco-friendly and mild conditions. However, innovation in the photoelectrochemical devices with high activity, stability, and selectivity for nitrogen-to-ammonia fixation has proven to be very challenging because nitrogen reduction reaction competes with the hydrogen evolution reaction, which occurs preferentially on the photocathode surface at a comparable thermodynamic potential. Thus, we have designed a unique aerophilic-hydrophilic heterostructured Si-based photocathode for improving the energy conversion efficiency. The aerophilic-hydrophilic heterostructure provides a new insight on designing efficient and robust photocathodes for nitrogen fixation.